The luminescent quantum efficiency of Cr³⁺ ions in co-doped crystals of LiNb0<syb>3 : ZnO determined by simultaneous multiple-wavelength photoacoustic and luminescence experiments - Torchia, Gustavo Adrián (2001)
In this paper, the luminescent quantum efficiency of Cr³⁺ ions in co-doped crystals of LiNb03: ZnO: Cr³⁺ is determined by using a method based on simultaneous multiple-wavelength measurement of photoacoustic and luminescence signal after pulsed laser excitation. The quantum efficiency found in this lattice was (10 ±4)% . This result was compared with the value found from the study of the lifetime in terms of the temperature of the luminescent levels involved. In this last case, two non-equivalent crystal sites were found for Cr³⁺ ions, and two fluorescence quantum yields were determined. After the estimation of the concentration of each site by electron paramagnetic resonance experiments, the averaged fluorescence quantum yield value was (9 ± 2)% in agreement with the previous result.